A potential therapeutic effect of catalpol in Duchenne muscular dystrophy revealed by binding with TAK1. Issue 5 (31st August 2020) - Xu, Dengqiu; Zhao, Lei; Jiang, Jingwei; Li, Sijia; Sun, Zeren; Huang, Xiaofei; Li, Chunjie; Wang, Tao; Sun, Lixin; Li, Xihua; Jiang, Zhenzhou; Zhang, Luyong
Abstract : Background: Duchenne muscular dystrophy (DMD) is a progressive muscle disease caused by the loss of dystrophin, which results in inflammation, fibrosis, and the inhibition of myoblast differentiation in skeletal muscle. Catalpol, an iridoid glycoside, improves skeletal muscle function by enhancing myogenesis; it has potential to treat DMD. We demonstrate the positive effects of catalpol in dystrophic skeletal muscle. Methods: mdx (loss of dystrophin) mice ( n  = 18 per group) were treated with catalpol (200 mg/kg) for six consecutive weeks. Serum analysis, skeletal muscle performance and histology, muscle contractile function, and gene and protein expression were performed. Molecular docking and ligand–target interactions, RNA interference, immunofluorescence, and plasmids transfection were utilized to explore the protective mechanism in DMD by which catalpol binding with transforming growth factor‐β–activated kinase 1 (TAK1) in skeletal muscle. Results: Six weeks of catalpol treatment improved whole‐body muscle health in mdx mice, which was characterized by reduced plasma creatine kinase ( n  = 18, −35.1%, P <  0.05) and lactic dehydrogenase ( n  = 18, −10.3%, P <  0.05) activity. These effects were accompanied by enhanced grip strength ( n  = 18, +25.4%, P <  0.05) and reduced fibrosis ( n  = 18, −29.0% for hydroxyproline content, P <  0.05). Moreover, catalpol treatment protected against muscle fatigue and promoted muscle recovery in the tibialis anterior (TA) and diaphragm (DIA) muscles ( n  = 6, +69.8%, P <  0.05 and + 74.8%, P <  0.001, respectively), which was accompanied by enhanced differentiation in primary myoblasts from DMD patients ( n  = 6, male, mean age: 4.7 ± 1.9 years) and mdx mice. In addition, catalpol eliminated p‐TAK1 overexpression in mdx mice ( n  = 12, −21.3%, P <  0.05) and primary myoblasts. The catalpol‐induced reduction in fibrosis and increased myoblast differentiation resulted from the inhibition of TAK1 phosphorylation, leading to reduced myoblast trans‐differentiation into myofibroblasts. Catalpol inhibited the phosphorylation of TAK1 by binding to TAK1, possibly at Asp‐206, Thr‐208, Asn‐211, Glu‐297, Lys‐294, and Tyr‐293. Conclusions: Our findings show that catalpol and TAK1 inhibitors substantially improve whole‐body muscle health and the function of dystrophic skeletal muscles and may provide a novel therapy for DMD.